The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.maturitas.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behaviour and suicide prevention in later life

Abstract: Despite a general decline in late life suicide rates over the last 30 years, older people have the highest rates of suicide in most countries. In contrast, non-fatal suicidal behaviour declines with age and more closely resembles suicide than in younger age groups. There are difficulties in the detection and determination of pathological suicidal ideation in older people. Multiple factors increase suicide risk ranging from distal early and mid-life issues such as child abuse, parental death, substance misuse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 53 publications
3
61
0
4
Order By: Relevance
“…ACE (e.g., early abusive or neglectful parenting, high family conflict, parental loss, and other maltreatment) have also been found to impact cognitive performance in older adulthood (Luecken, 2006). Draper (2014) further suggests that cognitive difficulties associated with aging may contribute to perceived burdensomeness, a component of the interpersonal-psychological theory of suicide.…”
Section: Interpersonal Functioningmentioning
confidence: 97%
See 2 more Smart Citations
“…ACE (e.g., early abusive or neglectful parenting, high family conflict, parental loss, and other maltreatment) have also been found to impact cognitive performance in older adulthood (Luecken, 2006). Draper (2014) further suggests that cognitive difficulties associated with aging may contribute to perceived burdensomeness, a component of the interpersonal-psychological theory of suicide.…”
Section: Interpersonal Functioningmentioning
confidence: 97%
“…functional impairment in older age is associated with death by suicide (Conwell et al, 2011b;Draper et al, 2008;Draper, 2014). Several studies have found a strong association between physical, emotional, and sexual abuse and health problems in adulthood (Norman et al, 2012;Sachs-Ericsson et al, 2005;Springer, Sheridan, Kuo, & Carnes, 2007).…”
Section: Health Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has identified many factors associated with older adult suicidal ideation and behavior. One of the most salient is psychopathology, particularly major depression . Research in the United States, South Korean, Brazilian, and Australian older adults suggests that psychological distress generally and major depression specifically account for the most variance in models examining suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that 90% of older people who take their lives suffered from a psychiatric disorder[6] with depressive disorders being the most common psychiatric diagnoses of elderly suicide victims[7]. Furthermore, late life suicidal ideation is a risk factor for suicide [4, 8, 9], and executive dysfunction[10, 11], in particular impulsivity [12-14], and impairments in risk-sensitive decision making[14, 15] are associated with greater suicidal ideation in older adults. Given that these deficits in executive function (ED) are common in depressed older adults[16] and is related to suicidal ideation[11, 17], identifying older adults with depression and ED and providing them with interventions that target executive deficits may be one way to correct the trends in death by suicide in those over the age of 65.…”
Section: Introductionmentioning
confidence: 99%